2018
DOI: 10.1111/rssc.12322
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Patterns of Demand in Bike Sharing Systems Via Replicated Point Process Models

Abstract: Summary Understanding patterns of demand is fundamental for fleet management of bike sharing systems. We analyse data from the Divvy system of the city of Chicago. We show that the demand for bicycles can be modelled as a multivariate temporal point process, with each dimension corresponding to a bike station in the network. The availability of daily replications of the process enables non‐parametric estimation of the intensity functions, even for stations with low daily counts, and straightforward estimation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 38 publications
(60 reference statements)
0
30
0
Order By: Relevance
“…, T m iid ∼ f , where f (t) = λ(t)/τ is a density function and τ = T 0 λ(s) ds is a scalar [10], also referred to as intensity factor. Point process techniques have recently also been successfully applied for bike rentals as events, aiming at the analysis of repeated observations of the bike rental point process [15], and the spatial distribution of street robberies [14].…”
Section: Local Fréchet Regression For Point Processes As Responsesmentioning
confidence: 99%
“…, T m iid ∼ f , where f (t) = λ(t)/τ is a density function and τ = T 0 λ(s) ds is a scalar [10], also referred to as intensity factor. Point process techniques have recently also been successfully applied for bike rentals as events, aiming at the analysis of repeated observations of the bike rental point process [15], and the spatial distribution of street robberies [14].…”
Section: Local Fréchet Regression For Point Processes As Responsesmentioning
confidence: 99%
“…Most of these studies focus on how socioeconomic, spatial, and behavioral factors such as bike accessibility (the distance between use and station) and availability (possibility to find a bike) (Kabra et al, 2018), customer characteristics (Guo et al, 2017;Ji et al, 2017), behaviors (Li et al, 2018) and travel patterns (Du and Cheng, 2018), and built environment (Zhang et al, 2017)) could affect the adoption and use of sharing bikes (Efthymiou et al, 2013;Yang and Long, 2016). Since the spatial and temporal imbalance between demand (Gervini and Khanal, 2019;Zhou et al, 2018) and (re)distribution (Ho and Szeto, 2017;Li et al, 2016) of sharing bikes is identified as the key to successful SBP development, some researchers have used different repositioning technologies and models to optimize the station position and address congestion or starvation issues of IT-based SBP (Forma et al, 2015;Ghosh et al, 2017;Szeto and Shui, 2018). This is of particular importance for DSBs due to their flexibility without docking stations, so demand forecasting (Xu et al, 2018), static (Liu et al, 2018) and dynamic repositioning problems (Shui and Szeto, 2018), optimizing location (Sun et al, 2019) and optimizing transportation planning (Sayyadi and Awasthi, 2018) are the key focuses of DSBs research as well in the transportation literature.…”
Section: Figmentioning
confidence: 99%
“…In this way, we are able to explicitly model the functional nature of the data (Bouveyron et al 2015) that would be lost with a simpler approach. Previous works on mobility data have already used FDA to model, for instance, the number of vehicles passing through a specific location (Chiou 2012; Guardiola et al 2014;Crawford et al 2017), or the bike sharing demand at different bike stations (Bouveyron et al 2015;Gervini and Khanal 2019); Torti et al 2021). Differently from other works, however, we mix motifs from FDA and network theory and we represent the road network of Lombardy as a graph evolving over time.…”
Section: Introductionmentioning
confidence: 99%